2005
DOI: 10.1111/j.1525-1497.2005.0076.x
|View full text |Cite
|
Sign up to set email alerts
|

The validity of a single-question self-report of erectile dysfunction

Abstract: OBJECTIVE:To determine how well a single question of self-reported erectile dysfunction compares to a gold standard clinical urologic examination. DESIGN AND SETTING:Clinical validation study nested within the Massachusetts Male Aging Study (MMAS), which is an observational cohort study of aging and health in a population-based random sample of men.MEASUREMENT: During an in-person interview, men were asked to respond to a single-question self-report of erectile dysfunction. A subsample of MMAS participants was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(110 citation statements)
references
References 34 publications
2
107
0
1
Order By: Relevance
“…This single, self-reported question has previously been validated for clinical erectile dysfunction. 7 Using an approach similar to that used in previous studies, 8 we considered men who responded "never able" or "sometimes able" to have erectile dysfunction and considered those who responded "usually able" or "always or almost always able" to have normal erectile function.…”
Section: Methodsmentioning
confidence: 99%
“…This single, self-reported question has previously been validated for clinical erectile dysfunction. 7 Using an approach similar to that used in previous studies, 8 we considered men who responded "never able" or "sometimes able" to have erectile dysfunction and considered those who responded "usually able" or "always or almost always able" to have normal erectile function.…”
Section: Methodsmentioning
confidence: 99%
“…All patients were re-evaluated using the Sexual Health Inventory for Men questionnaire for married cases, 20 and the single question self-report of ED was used for single cases. 21 Local examination was carried out for all patients to detect penile deviation and fibrotic scaring. Patients with ED were evaluated by CDU.…”
Section: Follow-upmentioning
confidence: 99%
“…Clinical assessment tools have been noted to potentially be oversensitive and classify people from the general population as dysfunctional when they may not have perceived themselves as such, 21 and hence these assessment measures were deemed inappropriate for use in this study. It has been demonstrated that single-item measures of self-reported experiences of ED are able to predict clinically diagnosed ED with reasonable accuracy; 22 however, it is noted that validated measures of ED would be more appropriate and would have allowed comparison of participants' subjective ratings against a validated objective rating scale. Greater confidence could be placed in the causative nature of the relationships in the current study through the use of a longitudinal study design and through use of matched samples.…”
Section: Limitationsmentioning
confidence: 99%